Synaptopathy in Guinea Pigs Induced by Noise Mimicking Human Experience and Associated Changes in Auditory Signal Processing - Xia, Li; Ripley, Sara; Jiang, Zhenhua; Yin, Xue; Yu, Zhiping; Aiken, Steve J.; Wang, Jian (Frontiers in Neuroscience, 2022)
Noise induced synaptopathy (NIS) has been researched extensively since a large amount of synaptic loss without permanent threshold shift (PTS) was found in CBA mice after a brief noise exposure (Kujawa et al., 2009). However, efforts to translate these results to humans have met with little success—and might not be possible since noise exposure used in laboratory animals is generally different from what is experienced by human subjects in real life. An additional problem is a lack of morphological data and reliable functional methods to quantify loss of afferent synapses in humans (see reviews of (Aedo et al., 2020; Hesse et al., 2019; Liberman et al., 2017; Parthasarathy et al., 2019)). Based on evidence for disproportionate synaptic loss for auditory nerve fibers (ANFs) with low spontaneous rates (LSR) (Furman et al., 2013; Song et al., 2016), coding-in-noise deficits (CIND) have been speculated to be the major difficulty associated with NIS without PTS (Henry, 2022; Kobel et al., 2017; Liberman et al., 2017). However, no robust evidence for this is available in humans or animals. This has led to a re-examination of the role of LSR ANFs in signal coding in high-level noise (see review (Carney, 2018)). The fluctuation profile model has been proposed to support a role for high-SR ANFs in the coding of high-level noise in combination with efferent control of cochlear gain. This study aimed to induce NIS by a low-level, intermittent noise exposure mimicking what is experienced in human life and examined the impact of the NIS on temporal processing under masking. It also evaluated the role of temporal fluctuation in evoking efferent feedback and the effects of NIS on this feedback.